A comprehensive review on the anticancer potential of bacteriocin: preclinical and clinical studies - Goh, Kar Shin; Ng, Zhang Jin; Halim, Murni; Oslan, Siti Nurbaya; Oslan, Siti Nur Hazwani; Tan, Joo Shun (Springer, 2022)
Cancer remains one of the key causes of mortality globally, in spite of the availability of advanced detection and treatment strategies. Conventional cancer therapies have non-selectivity to the target cells. Secondly, conventional cancer therapies are proved to cause various side effects during the treatment. Lastly, cancer cells are known to develop resistance to the currently available therapies. Therefore, there is a demand for a novel therapy for various types of cancer. Some of the bacteriocins have been reported to have an anti-cancer effect against various types of cancer cells. Bacteriocins are proteins synthesized by bacterial ribosomes. They have shown high selectivity toward the cancer cells and low cytotoxicity toward normal cells. This makes them a promising anticancer candidate to replace or combine with conventional therapeutic agents. In this review, the latest studies on the selectivity of bacteriocins against cancer cells and their anticancer activities in preclinical and clinical studies will be discussed.